Innovations in Development : Where Traditional Markets Fail - Walji, Aleem (2012)
As we think about the last several decades and what has really moved the needle in international development, we can't help but acknowledge the revolution in financial services to the poor that has grown into the multi-billion dollar micro-finance industry.